(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The main aim of this paper is a comparative analysis of the human capital profitability in companies operating in tourism industry in the municipality Mielno. The ratio analysis used efficiency indicators of human capital such as: the profitability of the labor cost index HCR CFTE and PTFE. It was assumed that investigated companies support development of human capital, but the achieved profitability varies in both companies.